2023
DOI: 10.1111/head.14607
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities in migraine are not mediated by a dysfunction of the glymphatic system—A diffusion tensor imaging magnetic resonance imaging study

Raffaele Ornello,
Federico Bruno,
Ilaria Frattale
et al.

Abstract: ObjectiveWe assessed whether brain magnetic resonance imaging (MRI) markers of glymphatic function are altered in patients with migraine and brain white matter hyperintensities (WMHs).BackgroundThe glymphatic system is responsible for the outflow of waste products from the brain. An impaired glymphatic system has been associated with WMH; however, this impairment has not been shown in patients with migraine.MethodsThe present cross‐sectional study included consecutive patients with migraine from a single terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Our data further support the potential use of the DTI-ALPS index in the evaluation of subjects with RCVS regarding clinical impacts and implicate the potential role of glymphatics in pain modulation. Several recent studies also enhanced the roles of glymphatic system in headache disorders (Supplementary Table 9 in Additional file 1 ) [ 19 , 31 , 32 , 49 55 ]. Nevertheless, since some studies depicted normal glymphatic functions in certain headache disorders, including episodic migraine [ 19 , 52 ] and new daily persistent headache, [ 24 ] and some demonstrated contradictory findings, [ 32 ] the potential mechanism of glymphatics in pain or headache modulation remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Our data further support the potential use of the DTI-ALPS index in the evaluation of subjects with RCVS regarding clinical impacts and implicate the potential role of glymphatics in pain modulation. Several recent studies also enhanced the roles of glymphatic system in headache disorders (Supplementary Table 9 in Additional file 1 ) [ 19 , 31 , 32 , 49 55 ]. Nevertheless, since some studies depicted normal glymphatic functions in certain headache disorders, including episodic migraine [ 19 , 52 ] and new daily persistent headache, [ 24 ] and some demonstrated contradictory findings, [ 32 ] the potential mechanism of glymphatics in pain or headache modulation remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…182 However, the median ALPS-index was reported to be similar in patients with and without white matter hyperintensities. 183 Another major problem with the DTI-ALPS method is that it can only evaluate the white matter outside the lateral ventricles in an image section that includes the body of the lateral ventricles. The ALPS method cannot evaluate perivascular diffusivity in other regions where the PVS does not run in the x-, y-, or z-axis directions.…”
Section: Controversy In Dti-alps Methodsmentioning
confidence: 99%
“…It has been suggested that CSD, the surrogate of migraine aura could determine, through the vasoconstriction of pial and penetrating arteries, a spreading ischemia and the appearance of WMHs at MR [ 93 ]. For these reasons, it could be postulated that the WMHs in patients suffering from migraine represent a consequence of the dysfunction of the GS [ 94 ]. To evaluate whether WMHs in migraineurs are associated with the GS dysfunction, Ornello et al used the DTI-ALPS index.…”
Section: Human Findingsmentioning
confidence: 99%
“…To evaluate whether WMHs in migraineurs are associated with the GS dysfunction, Ornello et al used the DTI-ALPS index. Using this technique, the authors did not find that GS dysfunction was associated with WMHs in patients with migraine [ 94 ].…”
Section: Human Findingsmentioning
confidence: 99%